AdS3×S3 magnons in the symmetric orbifold - Matthias R. Gaberdiel; Dennis Kempel; Beat Nairz (Journal of High Energy Physics)
Abstract The AdS3 × S3 excitations of string theory on AdS3 × S3 × T 4 $$ {\mathbbm{T}}^4 $$ are identified with certain collective modes in the dual symmetric orbifold. Our identification follows from a careful study of the conformal eigenstates in the perturbed orbifold theory. We find that, in addition to the fractional torus modes (that correspond to the torus excitations in the dual AdS spacetime), there are ‘long’ collective eigenmodes that involve a superposition of products of fractional torus modes, and that are in natural one-to-one correspondence with the expected AdS3 × S3 excitations. These collective modes are deformations of (fractional) N $$ \mathcal{N} $$ = 4 modes, to which they reduce for integer momentum.